A new epistemic in the Peruvian university: Mental revolution towards university 3.0 - Loayza Maturrano, Edward Faustino (2024)
Abstract The University as an institution has suffered the impact of the new advances in Information and Communication Technology (ICT) and the Internet. The purpose of this theoretical approach is to explore, from a postmodern and posthumanist perspective, philosophical-epistemological reflections on the new scenarios through which the Peruvian university is going and will go through to reorient its goals: as a challenge and ontological objective, in the face of the renewed demands of society. of the third millennium. The methodology used is qualitative through a proposal of discourse analysis and its own argumentative apparatus. The result assumes the need to initiate a change in the conception of the university and promote a mental revolution in all the agents involved in the university institutional environment.